PENGARUH IMPLEMENTASI MANAGEMENT BY OBJECTIVES TERHADAP PRODUKTIVITAS KARYAWAN (Studi Kasus Pada PT. Findora Internusa – Cirebon Jawa Barat) - Zulmauli Bahri; Tasya Aspiranti; Rusman Frendika (FEB Universitas Sam Ratulangi Manado, 2023)
This study aims to determine the effect of implementing management by objectives on employee productivity with a case study at PT. Findora Internusa Cirebon. The data used in this study is primary data, namely responses to questionnaires from 50 respondents. The research method used is a quantitative method with a descriptive verification research approach. The analytical method used in this study is multiple linear regression analysis using the SPSS Version 25 for windows program. The results of the study show the implementation of job related objectives, growth objectives, tasks and projects and targets and values variables on productivity carried out at PT. Findora Internusa is in the high category. Simultaneous testing of the influence of job related objectives, growth objectives, tasks and projects, and targets and values has a positive and significant effect on employee productivity. Partially job related objectives (X1) and tasks and projects (X3) have a positive but not significant effect on employee productivity. Meanwhile, for growth objectives (X2) and targets and values (X4) variables, there is a positive and significant effect on employee productivity. Keywords : Management By Objectives, Job Related Objectives, Growth Objectives , Tasks and Projects, Targets and Values and Productivity